Effectiveness of Expressive Writing in the Reduction of Psychological Distress During the COVID-19 Pandemic: A Randomized Controlled Trial - Vukčević Marković, Maša; Bjekić, Jovana; Priebe, Stefan (Frontiers in Psychology, 2020)
Objective:Due to the wide impact of the COVID-19 pandemic on mental health, the need for scalable interventions that can effectively reduce psychological distress has been recognized. Expressive writing(EW) can be beneficial for different conditions, including depression, suicidal ideation, and coping with trauma. Therefore, we aim to assess the applicability and effectiveness of an online format of EW in the reduction of psychological distress in the context of COVID-19. Methods:In this parallel-group, randomized controlled trial, participants (n = 120) were randomly allocated to (1)the intervention group – who completed five EW sessions over the two-week period, or (2)the control group - who received treatment as usual (TAU). Participants were assessed for primary and secondary outcome measures at baseline, posttreatment and follow-up one month after the treatment. The primary outcome was severity of psychological distress assessed at posttreatment, operationalized as Depression Anxiety Stress Scale (DASS) summary score. Secondary outcomes were severity of depression, anxiety, and stress (DASS subscale scores), well-being (WHO-5), subjective perception of quality of life (SQOL) and subjective evaluation of difficulties coping with pandemic, which were also assessed at posttreatment. Per protocol, analysis was conducted with available cases only. Results:A less favorable outcome was found in the intervention group on psychological distress, and symptoms of stress, after controlling for baseline scores. Increased stress was recorded in the treatment group, with no effect in the control group. There was no significant difference between the groups on depression, anxiety, wellbeing, and subjective quality of life. No group effect for any of the outcomes measures was recorded at follow up. Additional analysis revealed moderation effects of age and gender with older and male participants scoring higher on distress measures. Conclusion:Engaging in EW during the pandemic was found to elevate stress, thus when applied in the context of the Covid-19 pandemic, it may be harmful. Hence, EW or similar self-guided interventions should not be applied without prior evidence on their effects in the context of a pandemic and similar stressful and unpredictable circumstances. Trial registration: This study is approved by the Institutional Ethics Committee (#2020-20) and a trial has been registered at the ISRCTN:https://www.isrctn.com/ISRCTN17898730.